Harnessing endogenous signals from hepatocytes using a low volume multi-well plate. Issue 5 (29th March 2017) - Gheibi, Pantea; Son, Kyung Jin; Stybayeva, Gulnaz; Revzin, Alexander
Abstract : We demonstrate that hepatocytes in low volume microtiter plates upregulate HGF and other endogenous signals. Abstract : Hepatocytes are highly differentiated epithelial cells that lose their phenotype and function when removed from the in vivo environment. Given the importance of hepatic cultures for drug toxicity, bioartificial liver assist devices and basic biology studies, considerable efforts have been focused on the maintenance of hepatic function in vitro . The methods used to date include co-cultivation of hepatocytes with stromal cells, organizing these cells into spheroids and imbedding them into bioactive gels. Our team has recently demonstrated that primary rat hepatocytes confined to microfluidic channels in the absence of convection maintained the epithelial phenotype through upregulation of endogenous signals including hepatocyte growth factor (HGF). The objective of the present study was to transition from microfluidic devices, which are somewhat specialized and challenging to use, towards low volume multiwell plates ubiquitous in biology laboratories. Using a combination of 3D printing and micromolding we have constructed inserts that can be placed into standard 12-well plates and can be used to create low volume culture conditions under which primary hepatocytes maintained a differentiated phenotype. This phenotype enhancement was confirmed by hepatic function assays including albumin synthesis and expression. Importantly we confirmed upregulation of HGF inside the low volume culture plates and demonstrated that inhibition of HGF signaling degraded the hepatic phenotype in our cell culture platform. Overall, this study outlines a new cell culture system that leverages the low volume effects of microfluidic channels in a multiwell plate format. Beyond hepatocytes, such a system may be of use in the maintenance of other difficult-to-culture cells including stem cells and primary cancer cells.